Impact of the Asian Economic Crisis on Training Intentions and Outcomes - LEE, Soo-Hoon (Institutional Knowledge at Singapore Management University, 2003)
We tested the notion that employability is an antecedent to training intentions and outcomes by investigating if the Asian economic crisis motivated workers to go for more training. The severity of the crisis was operationalized in two ways. First, we compared the training intentions and actual training undertaken by employees during the crisis and during the recovery phase. Secondly, because Thailand was more severely affected by the crisis, we compared the training intentions and actual training undertaken between Thai and Singaporean workers. Regression analyses were used to investigate if workers' training intentions and actual training undertaken were the result of workers' perceptions of the relative economic benefits of training, the length of the time they took to find a job, or their perceptions of the rate of change in their job requirements. The results indicated that workers undergoing an economic crisis adjusted their training attitudes and behaviors to remain employable. Specifically, during the recession, employees were more willing to undergo training and actually spent more time undergoing training. Although Singaporean workers indicated a greater willingness to undergo training, this was not shown in their actual training behavior. Thai workers who faced a more severe economic crisis underwent more training programs. The results are explained by Becker's [Becker, G. S. (1964). Human Capital. New York: National Bureau for Economic Research] theory of human capital.